Ferramentas tecnológicas na representação descritiva de documentos: abordagem como conteúdo e como instrumentos - Tabosa, Hamilton Rodrigues (2012)
Here are some reflections on the need for knowledge of new tools used in information processing, in view of the teaching of descriptive representation, and show the metadata as the enablers of descriptive cataloging, and how teaching is being done in the course of cataloging Librarianship, Federal University of Ceará - Fortaleza Campus - and its implications. As a methodology, first performed a literature on the subject, by which it was possible to have access to the work of theorists like Arellano, Assumption, Lancaster, among others. We undertook a study of the proposed new cataloging code called Resource Description and Access (RDA), made by the Joint Steering Committee for Revision of AACR (JSC AACR), responsible for revision of AACR, because, although still in the process of drafting should replace the AACR soon, so warn about the need for knowledge of this tool by teachers and librarians cataloging.